Marvell, Europe, and Social Negotiations – Introduction. Issue 1 (10th September 2018) - Chardin, Jean-Jacques; Curelly, Laurent
Abstract : This is the introduction to the second volume of Marvell and Europe, guest-edited by Jean-Jacques Chardin and Laurent Curelly.